PENGELOLAAN KEUANGAN DESA BERDASARKAN PERMENDAGRI NO. 113 TAHUN 2014 TENTANG PEDOMAN PENGELOLAAN DANA DESA DAN PERBUP NO. 8 TAHUN 2018 TENTANG ALOKASI DANA DESA (Studi Empiris: Pemerintah Desa Embalut Kabupaten Kutai Kartanegara) - Muhammad Kadafi, SE., M.SA; Diyah Permana; Boby Mutakin (Politeknik Negeri Samarinda, 2019)
The objectives achieved in this study were to determine the application of Embalut Village financial management based on Permendagri Number 113 of 2014 concerning village financial management and Perbup Number 8 of 2018 concerning village fund allocation. For problem solving methods this research was conducted by combining observations, interviews, documentation and triangulation theory. Collecting data in this study using in-depth interviews, which are assisted by a recorder. The results of the discussion that have been described are: (a) village financial planning has been carried out with the principles of community participation and openness, (b) in the implementation of the village government has applied the principle of accountability for revenues and expenditures, but can be seen from the realization of the implementation of the budget allocation for village funds have not been optimally absorbed, especially in the field of implementation of development activities, (c) the administration has been carried out and is periodically accounted to the village head and the community, (d) reporting on the realization of the APBDesa implementation has been submitted to the community as a form of the process of implementing the APBDesa implementation, (e) for accountability reports on the realization of the APBDesa the village head has also submitted to the Regent at the end of the fiscal year. Keywords: Human Resource Accounting, Public Sector Accounting, Intangible Assets, Financial Statement.